The Influence Of Leadership And Work Discipline On The Performance Of Employees At The Department Of Transportation, South Lampung Regency - Djuanda; Habiburahman; Haninun (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
Employee performance is a key factor in the success of government agencies in providing effective public services. Leadership and work discipline are considered two important variables that play a role in improving the performance of the apparatus. This study aims to analyze the influence of leadership and work discipline on the performance of employees at the South Lampung Regency Transportation Office, both partially and simultaneously. The study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to employees and analyzed using multiple linear regression. The results of the study show that leadership has a positive and significant effect on employee performance, contributing 30.6%. Work discipline also has a positive and significant effect on employee performance, contributing 44.1%. Simultaneously, leadership and work discipline have a significant impact on employee performance, contributing 57.3%. This finding indicates that improving the quality of supportive leadership and consistently applying work discipline can optimally enhance employee performance. Therefore, government institutions need to strengthen effective leadership practices and structured work discipline systems to improve the quality of public service.